The introduction of new product qualities by incumbent firms: market proliferation versus cannibalization - Ralph Siebert (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2003)
This study analyzes the optimal provision of goods in a market characterized by vertical product differentiation. We consider a duopoly model in which incumbents may introduce a new product with certain quality, and decide whether to keep or to withdraw the existing product from the market. We find that the strategic and cannibalization effects dominate, such that no room is left for discrimination among consumers. The innovator always withdraws the existing product from the market, in order to reduce price competition and to avoid cannibalizing its new product demand. In contrast to horizontally differentiated markets, firms are better off not to offer a range or interval of product qualities in vertically differentiated markets. Hence, firms fare better, despite offering a smaller variety of goods. – – Diese Studie analysiert das optimale Angebot von Guetern, die sich in der Qualitaet untescheiden. Wir betrachten ein Modell, in dem zwei insaessige Unternehmen neue Produkte mit unterschiedlicher Qualitaet in den Markt einfuehren koennen. Zudem koennen die Innovatoren entscheiden, ob ihre existierenden Produkte weiterhin im Markt angeboten oder abgezogen werden sollen. Wir zeigen, dass strategische Effekte und Kannibalisierungseffekte keine Diskriminierung zwischen den Konsumenten zulassen. Der Innovator zieht das existierende Produkt immer aus dem Markt, um einen erhoehten Preiswettbewerb und eine Kannibilisierung der eigenen Nachfrage zu vermeiden. Im Gegensatz zu horizontal differenzierten Maerkten, stellen sich Unternehmen in vertikal differenzierten Maerkten besser, eine geringere Produktvielfalt anzubieten.
Keywords: L11; L13; O31; O32; 330; Asymmetric Firms; Cannibalization; Market Proliferation; New Product Introduction; Product Innovation; Vertical Product Differentiation